Impact of SMEs strategy on loyalty: the hairdresser case - Ángel López-Jáuregui; Mercedes Martos-Partal; Jose María Labeaga (Spanish Journal of Marketing-ESIC, 2019)
Purpose – This study aims to propose a theoretical framework and provide empirical evidence on the most successful marketing strategies for obtaining behavioural loyalty in small and medium enterprises (SMEs). Design/methodology/approach – The data are based on 475 telephone surveys conducted among Spanish hairdressers. The authors have used ordinary least squares to estimate the empirical model. Findings – Pricing, services and communication (Web page and in-store communication) are the main drivers of customer loyalty. SMEs have to be cautious with the use of social networks to avoid damaging loyalty. In addition, those positioned at high-price segments should pay more attention to communication on the Web, and all companies should find a balance between in-store communication and the sale of products for use at home. Research limitations/implications – Further research should try to replicate the findings with data from consumers and firms. Practical implications – Service managers need to understand the optimal strategy to succeed in the market. The key insights of this study could also apply to other sectors, such as health, personal care and wellness services. Originality/value – Previous research focussed mainly on large companies, while the role of loyalty in the success of SMEs has been poorly studied, with focus only on the antecedents and the measurement of loyalty. This study contributes to the previous research by analysing the effect of the strategy (price, range of services, communication, size and location) in the achievement of loyalty in SMEs.